The role of Māori community gardens in health promotion: a land-based community development response by Tangata Whenua, people of their land. (April 2019) - Hond, Ruakere; Ratima, Mihi; Edwards, Will
For Māori in Aotearoa New Zealand, land is not only an economic foundation but an anchor for tribal identity and a spiritual base. The forced alienation of Māori land since the 1800s, due to colonisation, has distanced communities from a direct relationship with their lands. There is little published research on Māori community gardens (māra) and their potential to reconnect Māori with ancestral lands. This study explores the motivations for developing māra and examines the role of māra in Māori health promotion. The paper describes findings from kaupapa Māori research that involved interviews with seven leaders of māra initiatives. Our findings suggest that the development of māra is motivated by a desire to empower Māori collectives towards a vision of vital communities thriving as Māori. Māra provide a rich site for community development grounded in a cultural connection to ancestral land. The utilization of ancestral lands enables groups to draw on a deep sense of shared identity that is rooted in those lands and fosters an intergenerational orientation. Māra offer activity linked with ancestral knowledge, customary practices and tribal connection. They provide opportunities to practice Māori language and cultural processes in functional everyday ways, and thereby strengthen a sense of commitment to protect cultural heritage as a resource for community life. Importantly, hands-on collective activity with shared decision-making, which is characteristic of māra, fosters social cohesion and collective efficacy. Overall our findings indicate that māra are land-centred community development initiatives that fit within the parameters of Māori health promotion and have much potential to contribute to achievement of Māori health promotion outcomes.